1968
DOI: 10.1090/s0002-9904-1968-12071-3
|View full text |Cite
|
Sign up to set email alerts
|

Toeplitz and Wiener-Hopf operators in 𝐻^{∞}+𝐶

Abstract: [lO] for earlier results) that is different from zero. In this note we describe in the linear span of iJ 00 and C. (This manifold is actually a closed subalgebra of Z, 00 .) We show that such a T Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Clearly supp φ is a closed subset. Now Douglas [3] has shown that a function in H°° 4-C is invertible if and only if its harmonic extension is bounded away from 0 in some annulus r < | z | < 1. Thus a unimodular function φ in H°° + C is invertible if and only if suppφ is empty.…”
mentioning
confidence: 99%
“…Clearly supp φ is a closed subset. Now Douglas [3] has shown that a function in H°° 4-C is invertible if and only if its harmonic extension is bounded away from 0 in some annulus r < | z | < 1. Thus a unimodular function φ in H°° + C is invertible if and only if suppφ is empty.…”
mentioning
confidence: 99%
“…[2]). Finally, expanding det Φ e along the last column, we obtain 14) which is equal to the (n, n) entry of the product (adj Φ e ) · (adj Ψ e ), where we denote by adj X ∈ A n×n the algebraic adjoint (adjugate) of a matrix X ∈ A n×n . Since Ψ e and Φ e are inverses of each other, then so are adj Φ e and adj Ψ e , and (2.14) is equal to 1, as claimed.…”
Section: One Sided Invertibility Of Matrices Over Commutative Ringsmentioning
confidence: 99%
“…By Theorem 1 there is a smallest such algebra, namely, the closed subalgebra of L 00 generated by H 00 and C. Somewhat unexpectedly, this algebra turns out to equal H 00 + C, the linear hull of H 00 and C (a fact which seems to have first been pointed out in [20]). The algebra H 00 + C arises, among other ways, in the study of Toeplitz operators [5], [8] and in a problem in prediction theory investigated by H. Helson and the author [14], [21]. In the present section I shall describe a few of the basic properties of tf 00 + C. The key observation needed to prove that H 00 + C is closed in L 00 is this: (*) If f is any function in C, then dist(/, A) = dist( ƒ, H °°).…”
Section: Contains a And Which Contains At Least One Riemann Integrablmentioning
confidence: 99%
“…Such a criterion for H 00 + C has been established and exploited by R. G. Douglas [5] ; it involves the behavior inside the unit disk of the harmonic extensions of the functions in H 00 + C. We let P denote the Poisson kernel : P(r, 0) = (1 -r 2 )/(l -2r cos 9 + r 2 ). The theorem is an easy consequence of the following lemma.…”
Section: Contains a And Which Contains At Least One Riemann Integrablmentioning
confidence: 99%